2020
DOI: 10.5334/gjgl.1078
|View full text |Cite
|
Sign up to set email alerts
|

Word order preferences and the effect of phrasal length in SOV languages: evidence from sentence production in Persian

Abstract: Heaviness (or phrasal length) has been shown to trigger mirror-image constituent ordering preferences in head-initial and head-final languages (heavy-late vs. heavy-first). These preferences are commonly attributed to a general cognitive pressure for processing efficiency obtained by minimizing the overall head-dependents linear distance-measured as the distance between the verb and the head of its left/right-most complement (Hawkins's Minimizing Domains) or as the sum of the distances between the verb and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This can schematically be seen in Figure 3. Evidence for a long-before-short preference has been found from production experiments in SOV languages (Yamashita and Chang, 2001;Ros et al, 2015;Faghiri and Samvelian, 2020). For example, in Japanese sentences 1a-1b, consisting of a short subject and a long object, Yamashita and Chang (2001) found that speakers produced more noncanonical (OSV) order sentences like 1b than the canonical (SOV) like 1a.…”
Section: Resultsmentioning
confidence: 99%
“…This can schematically be seen in Figure 3. Evidence for a long-before-short preference has been found from production experiments in SOV languages (Yamashita and Chang, 2001;Ros et al, 2015;Faghiri and Samvelian, 2020). For example, in Japanese sentences 1a-1b, consisting of a short subject and a long object, Yamashita and Chang (2001) found that speakers produced more noncanonical (OSV) order sentences like 1b than the canonical (SOV) like 1a.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis that longer dependents are preferentially placed in the periphery is primarily motivated by more general observations of dependency length minimization (DLM) (Ferrer i Cancho, 2004; Futrell et al., 2020; Gibson, 1998, 2000; Jing, Blasi, & Bickel, in press; Liu, 2008; Temperley, 2008). The core finding of DLM research is that speakers seek to minimize the total length of dependencies in a given structure because this reduces pressure on working memory and keeps adjacent information that belongs together (Choi, 2007; Faghiri & Samvelian, 2014, 2020; Futrell et al., 2020; Gibson et al., 2019; Hawkins, 1994; Ros, Santesteban, Fukumura, & Laka, 2015; Yamashita, 2002; Yamashita & Chang, 2001). One specific effect of this bears on the peripheral placement of long dependents: when dependents occur on the same side of their head, placing the shortest dependent closest to the verb reduces the total length of dependencies.…”
Section: Introductionmentioning
confidence: 99%